LABORATORY BLOOD TESTING IN PAEDIATRIC INTENSIVE CARE UNIT OF A UNIVERSITY HOSPITAL: ARE WE DOING IT APPROPRIATELY? - Sohail, Hafsa; Bibi, Shazia; Hakeem, Mahnaz; Haque, Anwar ul; Abbas, Qalab (Journal of Ayub Medical College Abbottabad, 2020)
Retrospective chart review of all children (aged-one month to 16yr) admitted in our paediatric intensive care from June to November 2016 was done to determine the indication of different laboratory tests. LBT indications were defined into: diagnostic/case findings/screening tests to make a diagnosis; haemostatic tests (to monitor function or identify before clinical signs and symptoms) and therapeutic /monitoring tests to get the level of drug directly or getting level of marker as a guide to therapy. Laboratory tests reports which were within normal range more than once were labelled as in-appropriate tests. In total 274 patients, Haemostatic tests were performed for mean of 35.18±56.72 times (range of 0-429), monitoring for mean of 9.38±20 times (range 0-165), and therapeutic tests (3.26±11.25). Most common tests included serum Sodium levels (7.83±12.73), Serum Potassium (8.19±12.80), bicarbonate (7.75±11.9). 13.40±9.11 tests were done on first day and 13.0±8.49/day tests were performed afterwards. Cumulatively 54.31±74.21 tests were performed/ patients out of which 18.5±37.82 were inappropriate. Keywords: Laboratory testing; PICU; Indications